A Patient Affected with Serous Ovarian/Peritoneal Carcinoma Carrying the FANCM Mutation - Adamantia Nikolaidi; Irene Konstantopoulou; Nikolaos Pistalmantzian; Florentia Fostira; Drakoulis Yannoukakos; Ilias Athanasiadis (Case Reports in Oncological Medicine)
We report a case of a 58-year-old female with ovarian cancer. The patient presented with ascites, and the biopsies revealed a low-grade adenocarcinoma, either a serous papillary ovarian cancer with peritoneal implants or a primary peritoneal carcinoma. She received neoadjuvant chemotherapy and after 5 cycles achieved partial response, and then, she underwent a total hysterectomy/bilateral salpingo-oophorectomy. The patient underwent germline gene-panel testing for the detection of mutations in cancer predisposing genes. A truncating mutation in the Fanconi anemia complementation group M (FANCM) gene was detected in heterozygosity, namely, p.Arg658Ter (c.1972C>T, rs368728266). The patient’s family history is unremarkable, with no reported cases of breast or ovarian cancer, a fact that can be attributed to the significant lower penetrance of FANCM mutations.